OP0240 How strong are the associations of spondyloarthritis-related comorbidities with ankylosing spondylitis, psoriatic arthritis and undifferentiated spondyloarthritis? a register-based study from sweden. (15th June 2017) - Bengtsson, K; Forsblad-d'Elia, H; Lie, E; Klingberg, E; Dehlin, M; Exarchou, S; Lindström, U; Askling, J; Jacobsson, LT
Abstract : Background: Spondyloarthritis (SpA), including ankylosing spondylitis (AS), psoriatic arthritis (PsA) and undifferentiated SpA (uSpA), is a cluster of rheumatic diseases with some common genetic risk factors. These genetic risk factors are likely to result in associations of varying degree with SpA-related comorbidities such as inflammatory bowel disease (IBD), psoriasis and anterior uveitis. There is also a known association between AS and conduction disturbances and aortic regurgitation. Comparative analyses in the same setting of the strengths of these associations with AS, PsA and uSpA are scarce. Objectives: To assess the strengths of the associations of different SpA-related comorbidities with a diagnosis of AS, PsA and uSpA. Methods: All patients, aged ≥18 years, with AS (n=3884), PsA (n=8706) and uSpA (n=2665) were identified 2001 through 2005, according to specified ICD codes from the Swedish Patient Register. The register contains diagnoses from all visits in inpatient and non-primary outpatient care. Each patient was matched by year of birth, sex and county to five general population (GP) controls identified in the Population Register. Occurrence of SpA-related comorbidities prior to 1 January 2006 were also retrieved from the Swedish Patient Register. Number and proportion of cases (n (%)) with a recorded SpA-related comorbidity prior to 1 January 2006 and corresponding prevalence ratio (PR) with 95% confidence interval (CI) were calculated, overall and stratified for sex. Results: PRs for SpA-related comorbidities were significantly elevated in all SpA subtypes compared to their matched GP controls (Table). PRs were substantially elevated in AS, intermediately elevated in uSpA, whereas only moderately increased in PsA. The results were similar in the sex-stratified analyses (not shown). Conclusions: The strongest associations of SpA-related comorbidities were seen with AS, closely followed by uSpA, compatible with a substantial shared etiology and phenotypical expression for patients given these two diagnoses, whereas the associations between PsA and the SpA-related comorbidities were considerably weaker. Disclosure of Interest: None declared